The hybridisation of conflict: A prospect theoretic analysis - Pieter Balcaen; Cindy Du Bois; Caroline Buts (Games, 2021)
Revisionist actors are increasingly operationalising a broad number of non-violent threats in their quest to change the status quo, popularly described as hybrid conflict. From a defensive point of view, this proliferation of threats compels nations to make difficult choices in terms of force posture and composition. We examine the choice process associated with this contemporary form of state competition by modelling the interactions between two actors, i.e., a defender and a challenger. As these choices are characterised by a high degree of uncertainty, we study the choice from the framework of prospect theory. This behavioural-economic perspective indicates that the defender will give a higher weight and a higher subjective value to conventional threats, inducing a higher vulnerability in the domain of hybrid deterrence. As future conflict will increasingly involve choice dilemmas, we must balance threats according to their probability of occurrence and their consequences. This article raises awareness regarding our cognitive biases when making these choices.
Keywords: 330; grand strategy; hybrid threats; prospect theory; state competition